Archaeological and Geomagnetic Implications of New Archaeomagnetic Intensity Data from the Early Bronze High Terrace 'Massif Rouge' at Mari (Tell Hariri, Syria). (5th June 2014) - Gallet, Y.; Butterlin, P.
Abstract : We present new archaeointensity data from the Mesopotamian city of Mari (Syria), in particular from the high terrace 'Massif Rouge' dated at c.2550bce . These data were obtained using the experimental protocol developed for the Triaxe magnetometer. They allow for increased confidence in a strong geomagnetic field intensity maximum during the 26th centurybce . They also show that the second urban phase of Mari ('ville II') was marked by a decrease in the geomagnetic field intensity. We use this evolution to propose a relative chronology between different ensembles of fragments, thus highlighting some renovations in the Royal Palace of ville II.